Implementasi Knowledge Management di Perpustakaan Keraton Sumedang Larang - -, Aswinna -; Salim, Tamara A. (FPPTI Jawa Tengah, 2021)
The Sumedang Larang Palace Library has a collection for the advancement of Sundanese culture and limited human resources are a critical threat to the organization. This research needs to be done to find out individual knowledge that becomes organizational knowledge, so it is necessary to conduct knowledge management research at the Sumedang Larang Palace Library. This study aims to identify the implementation of knowledge management in the Sumedang Larang Palace Library. The results show that the management of the library at the Sumedang Larang Palace Library is still simple. Tacit knowledge is stored by the library manager and has not been documented as explicit knowledge. This study provides several recommendations for the management of the Sumedang Larang Palace Library.